Faktor-faktor yang Mempengaruhi Kepuasan Pasien BPJS terhadap Pelayanan Keperawatan di Ruangan Rawat Inap Mawar RSUD Bangkinang Tahun 2016 - Nany Librianty (UIR Press, 2018)
Poor management and health care services BPJS health membership provided by the hospital to the patient has been realized to cause many losses for both the hospital and for the patient. This indication is significant, from the LB 1 report, if the disgruntled patient basically represents 25 other disenchanted patients . If every day there are 100 patients who complain, there are 2,500 patients who are disappointed with the service BPJS. The purpose of this study to determine the factors that affect patient satisfaction BPJS to nursing service. The design of this study was an analytic survey. Population in this research is all patient of BPJS at Inpatient Room of Mawar RSUD Bangkinang with amount of 60 people. Sampling technique is total sampling that is as much as 60 patient of BPJS inpatient room of Mawar RSUD Bangkinang. The measuring tool used is a questionnaire sheet. Analysis used Univariat and Bivariat. The result of research is therapeutic communication factor of nurse with patient satisfaction of BPJS with nursing service, with p value = 0,007 <0,05 POR = 0,729. There is relationship of nurse competence factor with patient satisfaction BPJS, with p value = 0,001 <0,05 POR = 0,010. There was correlation factor of carring nurse with patient satisfaction BPJS with p value = 0,03 <0,05 POR = 0,627. It is expected to RSUD Bangkinang to further improve nursing service to patients by paying attention to how to communicate a good therapeutic, improve the competence of nurses and expected nurses always carring against patients.